Commercial Bank Net Interest Margins, Default Risk, Interest Rate Risk and off-balance sheet banking: A Case of Nepalese Commercial Banks - Khadka , Prem; Pradhan, Sumit (Nepalese Journal of Finance, 2024)
This study examines the impact of default risk, interest rate risk and off balance sheet activities on the profitability of Nepalese commercial banks. Return on assets and net interest margin are the selected dependent variables. The selected independent variables are spread rate, capital adequacy ratio, non-performing loan, loan loss provision, liquidity and off balance-sheet activities. The study is based on secondary data of 13 commercial banks with 104 observations for the study period from 2015/16 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual report of respective commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of spread rate, capital adequacy ratio, non-performing loan, loan loss provision, liquidity and off balance-sheet activities on the profitability of Nepalese commercial banks. The study showed that spread rate has a positive effect on return on assets and net interest margin. It means that increase in spread rate leads to increase in return on assets and net interest margin. Similarly, capital adequacy ratio has a positive effect on return on assets and net interest margin. It indicates that increase in capital adequacy ratio leads to increase in return on assets and net interest margin. Moreover, loan loss provision has a negative effect on return on assets. It shows that higher the loan loss provision, lower would be the return on assets. In contrast, off balance-sheet activities have a negative effect on return on assets and net interest margin. It means that increase in off balance-sheet activities lead to decrease in return on assets and net interest margin. Similarly, liquidity has also a negative effect on return on assets and net interest margin. It means that increase in liquidity leads to decrease in return on assets and net interest margin.